(untitled) (Biodiversitas Journal of Biological Diversity, 2016)
The objective of the study was to know the taxonomic structure of the genus of Zingiber based on cytological characters such as ratio of number, shape and size of chromosome. Zingiber specimens were mainly from Bogor botanical garden. There were seven species studied, Z. amaricans Nor., Z. aromaticum Val., Z. cassumunar Roxb., Z. gramineum Bl., Z. officinale Roxb., Z. ottensii Val. and Z. zerumbet (L.) J.E. Smith. Z. officinale (local name: Jahe) consinsting of 4 varieties, big ginger (jahe gajah), red ginger (jahe merah), small ginger (jahe emprit) and blue-dark browny ginger (jahe wulung). Species identification was based on the literature such as of Backer and Bakhuizen van den Brink (1968), Holttum (1950), and Burkill (1935). Semi permanent squash method using acetoorcein dye was used to prepare the sample (Darnaedi, 1991; Okada, 1981; Robert and Short, 1979). The results of the study indicate that the number of chromosomes of all species studied were the same, 2n=32. The length size of the first chromosome pair was about 2Î¼m. The shape of the chromosomes was mostly metacentric. Length and shape of each pair of chromosomes were hard to be determined accurately using this method, so that the chromosomal karyotype map unable to be constructed in this study. Giemsa C-banding method might be used to solve the problems. Â© 2000 Jurusan Biologi FMIPA UNS Surakarta